On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique